Implementation of Legal Sanctions for Perpetrators of BPJS Employment Contribution Embezzlement - Arsalina Fajrah; Sanco Simanullang; Habieb Pahlevi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the enforcement of legal sanctions against perpetrators of BPJS Employment contribution embezzlement, which undermines workers' rights and the stability of the social security system. The research employs normative juridical methods with a legislative approach, supported by secondary data from court decisions, books, and regulations. Findings indicate that the embezzlement of BPJS Employment contributions, regulated under Articles 374 and 64 of the Indonesian Penal Code, clearly constitutes a legal violation. Legal sanctions under Article 55 of Law Number 24 of 2011 prescribe a maximum penalty of 8 years imprisonment or a fine of IDR 1 billion. However, enforcement faces challenges, such as weak supervision and low legal awareness among offenders. This study recommends improving supervision mechanisms, imposing stricter sanctions, and providing legal education to employers.